2016
DOI: 10.1039/c6ra10221b
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the phase transition temperature of X-doped (X = Li, Na or K) VO2

Abstract: Vanadium dioxide (VO 2 ) is one of the most interesting thermochromic materials with a phase transition temperature of 340 K. Our first-principles calculation indicates that Li, Na or K dopants with a doping level of 1 atomic percentage could reduce the phase transition temperature of VO 2 by 43K, 49K, 94 K, respectively. In addition, the V-V chains feature the dimerization characteristics in the Li, Na or K doped VO 2 (R).The calculated electronic structures and optical properties indicate that K is as an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…The first dopant, sodium decreased the Tc to 57 C. Compared to Na doping, K dopant was found to be the most efficient one, as it offered a higher Tc reduction to 47 °C. These values are still higher than as reported by Cui et al26 who reported first-principle calculations on the basis of sodium and potassium doped VO2 films, can reduce the Tc by 49 K and 94 K per 1 at % dopant. Similarly, potassium resulted in a higher degree of reduction in the Tc, with 15 °C per 1.5 % dopant.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…The first dopant, sodium decreased the Tc to 57 C. Compared to Na doping, K dopant was found to be the most efficient one, as it offered a higher Tc reduction to 47 °C. These values are still higher than as reported by Cui et al26 who reported first-principle calculations on the basis of sodium and potassium doped VO2 films, can reduce the Tc by 49 K and 94 K per 1 at % dopant. Similarly, potassium resulted in a higher degree of reduction in the Tc, with 15 °C per 1.5 % dopant.…”
contrasting
confidence: 58%
“…Li, Na and K dopants were also investigated by calculation and K found to effectively decrease the Tc as well as improve the transmittance modulation in near infra-red region. Level of 1 at % could reduce the phase transition temperature of VO2 by 43 K, 49 K, 94 K, respectively 26 . To the best of our knowledge, these dopants have not been not reported in any experimental work yet.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, graphene/LiMn 2 O 4 , graphene/LiMnPO 4 , graphene/Li 3 V 2 (PO 4 ) 3 , graphene/Li 3 T 2 (PO4) 3 , graphene/Li 2 FeSiO 4 , graphene/Li 2 MnSiO 4 , graphene/V 2 O 5 , graphene/FePO 4 , graphene/FeF 3 , and graphene/LiNi 1/3 Co 1/3 Mn 1/3 O 2 have been explored as possible cathodes for rechargeable Li‐ion batteries. For instance, FeF 3 /graphene composites delivered a charge capacity of 155, 113, and 73 mAh g −1 at 104, 502, and 1040 mA g −1 current density, with stable cyclability for over 100 cycles, which was attributed to the buffering effect and lowered resistance from the graphene…”
Section: Li‐ion Batteriesmentioning
confidence: 99%
“…Like other works in ref. , our current calculations are performed without using the spin‐polarization.…”
Section: Methodsmentioning
confidence: 99%
“…For example, N‐doped VO 2 can effectively reduce the energy gap and lower the T c . Cui et al found that the K element can enhance the near‐infrared absorption of VO 2 and decrease the T c when they had studied the alkali metal‐doped VO 2 . The fourth main group elements of Si, Ge, Sn, and Pb‐doped VO 2 have also been investigated .…”
Section: Introductionmentioning
confidence: 99%